The inflamed biceps tendon as a pain generator in the shoulder: A histological and biomolecular analysis. (4th January 2019) - Schmalzl, J; Plumhoff, P; Gilbert, F; Gohlke, F; Konrads, C; Brunner, U; Jakob, F; Ebert, R; Steinert, AF
Introduction: The long head of the biceps (LHB) is often resected in shoulder surgery. However, its contribution to inflammatory processes in the shoulder remains unclear. In the present study, inflamed and noninflamed human LHBs were comparatively characterized for features of inflammation. Materials and methods: Twenty-two resected LHB tendons were classified into inflamed ( n = 11) and noninflamed ( n = 11) samples. For histological examination, samples were stained with hematoxylin eosin, Azan, van Gieson, and Masson Goldner trichrome. Neuronal tissue was immunohistochemically visualized. In addition, specific inflammatory marker gene expression of primary LHB-derived cell cultures were analyzed. Results: Features of tendinopathy, such as collagen disorganization, infiltration by inflammatory cells, neovascularization, and extensive neuronal innervation were found in the tendinitis group. Compared to noninflamed samples, inflamed LHBs showed a significantly increased inflammatory marker gene expression Conclusion: Structural and biomolecular differences of both groups suggest that the LHB tendon acts as an important pain generator in the shoulder joint. These findings can, on the one hand, contribute to the understanding of the biomolecular genesis of LHB tendinitis and, on the other hand, provide possibilities for new therapeutic approaches.